Energy sovereignty in Italian inner areas: Off-grid renewable solutions for isolated systems and rural buildings. (August 2016) - Menconi, Maria Elena; dell'Anna, Stefano; Scarlato, Angelo; Grohmann, David
Abstract: This paper deals with a compact system developed to assure energy independence to buildings located in inner rural areas: the Off-Grid Box. This system features a combination of techniques that assure the use of several renewable energy sources, their storage and the rationalization of consumption. This research studies the base model of the Off-Grid Box, which entails the presence of photovoltaic panels as the energy capture system. The aim of this research is to evaluate the opportunity of realizing a system to ensure energy autonomy of rural residential buildings. To achieve energy independence, for an isolated dwelling, this paper assesses the optimal storage systems that may be combined with a photovoltaic system. To this end, an Off-Grid Box has been installed in a residential unit in central Italy. Starting from the real case, two alternative energy storage scenarios were constructed. The results can be applied to a variety of geographical settings and prove the feasibility and strategic importance of total off-grid systems for individual residential units, when they are designed in integrated terms in the area to implement small-scale-smart-grids. In rural areas, these grids should also cater for small farming businesses that feature a different consumption distribution compared to dwellings. Highlights: A off-grid box has been developed for energy self-sufficient housing units . An approach to rationalize the energy production and the storage system is proposed. VRLA or Li-Ion energy storage systems are effective for houses in inner areas. Design smart microgrid is the key for energy autonomy of rural areas.